ChemInform Abstract: Planar Chiral Phosphoramidites with a Paracyclophane Scaffold: Synthesis, Gold(I) Complexes, and Enantioselective Cycloisomerization of Dienynes. Issue 29 (29th June 2016) - Wu, Zhiyong; Isaac, Kevin; Retailleau, Pascal; Betzer, Jean‐Francois; Voituriez, Arnaud; Marinetti, Angela
Abstract: Key structural feature of the new phosphoramidites is a paracyclophane scaffold in which two aryl rings are tethered by both a 1, 8‐biphenylene unit and a O—P—O bridge.